its wrong
Step-by-step explanation:
Subtract thats how you get it
Answer:
put a more clear pic
Step-by-step explanation:
Answer:
A) 5x + 2y = 22
B) -2x + 6y = 3 We'll multiply A) by -3
A) -15x -6y = -66 Then we'll add B)
B) -2x + 6y = 3
-17x = -63
x = 3.7058823529
y = 1.7352941178
Step-by-step explanation:
Answer:-45
Step-by-step explanation:this is how I do it: draw a line in the middle of the equal sign. Now its split in two parts. Do the opposite operation on the left side, so minus 6 from the left AND the right. Now it equals to y/3 = -15. Now times each side by 3 so the y stands alone. -15 times 3 equals -45. Y = -45. Sorry it's kinda hard to explain!